Analysis of Six Organophosphorus Pesticide Residues in Apples and Pears Using Cloud-point Extraction Coupled with HPLC-UV. (27th November 2019) - Zhang, Lijin; Chen, Fang; Zhang, Wenhuan; Pan, Canping
Abstract: A cloud-point extraction (CPE) method with Triton X-114 has been developed for analysis of six organophosphorus pesticides (OPPs) in apples and pears. In this CPE procedure, the effects of the surfactant volume, mass of sodium chloride, equilibrium temperature, equilibrium time, and pH on the extraction procedure were investigated. Under the optimal CPE conditions, the analytes were enriched 20-fold and the LODs dropped to 0.44–5.20 μg/kg. Furthermore, the proposed extraction method was validated by the correlation coefficient ( R 2 ) of the calibration curve, repeatability (RSD, n = 6), and fortified recoveries, which were 0.9967–0.9993, 2.7–6.5, and 74.7–104.5%, respectively. Based on these results, it could be concluded that the proposed CPE method with Triton X-114 was suitable for the effective extraction and enrichment of OPP residues in the apple and pear samples.